2019
DOI: 10.1159/000502332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dumbbell Exercise on Arteriovenous Fistula in Patients Undergoing Maintenance Haemodialysis: A Prospective Randomized Controlled Trial

Abstract: Background: Arteriovenous fistulas (AVF) have been the main vascular accesses for haemodialysis patients, but the maintenance after maturation poses serious challenges. Arm exercises promote the maturation of AVFs. However, few studies have evaluated the effect of arm exercise on matured AVF and addressed the intervention for late fistula failure. Objectives: The study was conducted to explore the effect of dumbbell exercise on mature AVF. Methods: 86 participants undergoing haemodialysis with AVFs were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Although our results demonstrated that experimental upper limb exercise programs did not increase DVD in patients with AVF, they indicated a significant improvement in DVBFR. These findings were supported by Mo et al, 12 who demonstrated that 3 months of an experimental exercise program using dumbbells for the upper limb with a functional AVF significantly improved blood flow when compared to the usual care group. We decided to maintain Mo et al 12 study in this analysis due to the exclusion of AVF with a diameter of the aneurysm >2 cm and due to exercises are performed on non-dialysis days at home, disregarding the dilation and increased blood flow mediated by hemodialysis and anticoagulant drugs.…”
Section: Discussionsupporting
confidence: 56%
“…Although our results demonstrated that experimental upper limb exercise programs did not increase DVD in patients with AVF, they indicated a significant improvement in DVBFR. These findings were supported by Mo et al, 12 who demonstrated that 3 months of an experimental exercise program using dumbbells for the upper limb with a functional AVF significantly improved blood flow when compared to the usual care group. We decided to maintain Mo et al 12 study in this analysis due to the exclusion of AVF with a diameter of the aneurysm >2 cm and due to exercises are performed on non-dialysis days at home, disregarding the dilation and increased blood flow mediated by hemodialysis and anticoagulant drugs.…”
Section: Discussionsupporting
confidence: 56%
“…Doctors, nurses, and researchers themselves supervise and guide patients during exercise intervention during dialysis and deal with emergencies when necessary. The graduate students themselves participate in the whole process of this research, including the signing of the informed consent form, the collection, sorting, and entry of various patient information and data [ 20 ].…”
Section: Research Objectmentioning
confidence: 99%
“…Dumbbell exercise is an economical and effective intervention that can maintain the function of AVF, especially in patients who may have reduced blood flow and have no indications for PTA. 91 …”
Section: Description Of the Consensusmentioning
confidence: 99%
“…Dumbbell exercise is an economical and effective intervention that can maintain the function of AVF, especially in patients who may have reduced blood flow and have no indications for PTA. 91 The European nursing guidelines indicated that allowing patients to prepare for HD more actively can improve their self-management ability, improve the sense of gain, and even prognosis. The guidelines state that simple exercises (such as pinching hands) are unlikely to produce any harmful results.…”
Section: Beraprost Can Be Selectively Used After Avf Surgery (2b)mentioning
confidence: 99%